A Lightweight Lap Time Measurement System for Alpine Ski Sport Using a TDMA-Based Linear Wireless Sensor Network - Hyung-Bong Lee; Ki-Hyeon Kwon; Lae-Jeong Park; Tae-Yun Chung; Qishi Wu (International Journal of Distributed Sensor Networks)
In Alpine ski sport, traditional lap time measurement systems record a skier's departure and arrival using time-of-day timers through wires, which is not cost effective in unofficial or training games. This paper develops a lightweight lap time measurement system using a wireless sensor network, which employs a practical TDMA-based linear wireless sensor network protocol for multihop communications in long strap-shaped environments where sensor nodes are linearly deployed. We evaluate the performance of this protocol through the implementation and deployment of the lap time measurement system. The experimental results show that the proposed protocol transmits data at a success rate of 99.66% and maintains the time synchronization errors between two adjacent nodes within 183  μ s without using any other time synchronization protocols. In an experimental deployment for a 1.5 km ski slope covered by 31 nodes, the system provides lap time measurements with a measurement error of 1.255 ms, which satisfies the official measurement error of 5.0 ms.